Stability of van der Waals FePX3 materials (X: S, Se) for water-splitting applications. (1st January 2023) - Sharma, Sandhya; Zeeshan, Hafiz Muhammad; Panahi, Mohammad; Jin, Yichen; Yan, Mouhui; Jin, Yukun; Li, Kexin; Zeller, Patrick; Efimenko, Anna; Makarova, Anna; Smirnov, Dmitry; Paulus, Beate; et al.
Abstract: The interaction of high-quality transition metal trichalcogenides (TMTs) single crystals FePX3 (X: S, Se) with water molecules is studied using near-edge x-ray absorption fine structure (NEXAFS) and x-ray photoelectron spectroscopy (XPS) in a wide range of temperature and partial pressure of H2 O. The physisorption nature of interaction between H2 O and FePX3 is found at low temperatures and relatively small concentrations of water molecules, that is supported by the DFT results. When temperature of the FePX3 samples and partial pressure of H2 O are increased, the interaction at the interface is defined by two competing processes—adsorption of molecules at high partial pressure of H2 O and desorption of molecules due to the increased surface mobility and physisorption nature of interaction. Our intensive XPS/NEXAFS experiments accompanied by DFT calculations bring new understanding on the interaction of H2 O with surface of a new class of 2D materials, TMTs, pointing to their stability and reactivity, that is important for further applications in different areas, like sensing and catalysis.